Aktivitas Minyak Jahe Merah (Zingiber Officinale var. rubrum) Terhadap Nyeri Inflamasi pada Mencit Balb-C dengan Induksi CFA (Completed Freund’s Adjuvant) (Activity of Red Ginger Oil (Zingiber officinale var. rubrum) on Inflammatory Pain in Mice Balb-C Wi - Fransiska Maria Christianty; Gati Dwi Sulistyaningrum; Fifteen Aprilia Fajrin; Diana Holidah (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Pain is a multidimentional experiences. Chronic pain is caused by inflammation. Nowdays, the treatment of chronic pain is still a challenge. Plants that known to have analgetic activity is red ginger (Zingiber officinale var. rubrum). This research observed the effect of red ginger oil on inflammatory pain. Inflammatory condition was induced by intraplantar injection of CFA (Completed Freund's Adjuvant). Twenty mice were divided into 4 groups i.e sham, negative control, red ginger oil in two different doses (100 and 200 mg/kg BW). Red ginger oil was administrated per oral once a day for seven consecutive days, a week after CFA injection. Latency time toward thermal stimulus was measured on days 0, 1, 3, 5, 7, 8, 10, 12, and 14 after CFA injection. Paw thickness at the ipsilateral site was also measured on days 0, 1, 3, 5, 7, 8, 10, 12 and 14 after CFA injection. The result showed that the administration of red ginger oil significantly increased latency time toward thermal stimulus compared to negative control. It also significantly reduced paw thickness especially at dose of 200 mg/kg BW. These findings suggested that administration of red ginger oil could treat the inflammatory pain, caused by CFA injection. Keywords: red ginger oil, inflammatory pain, CFA, hyperalgesia